PELAKSANAAN KUNJUNGAN KELAS UNTUK MENINGKATKAN KETERAMPILAN MENGGUNAKAN MEDIA AUDIOVISUAL BAGI GURU - Supriyanto Supriyanto (Intersections, 2022)
Abstract The aim of the research is to improve skills in using audiovisual media for teachers at SDN 1 Babaktul. The research subjects were 6 teachers. Data collection techniques with observation and documentation techniques. Data validation with triangulation techniques. Qualitative data analysis method. The results showed that the teacher's skill in using audiovisual media in the initial conditions was 47.62 (LOW) and the first cycle was 69.35 (ENOUGH) and in the last cycle it was 91.07 (VERY GOOD). Classical completeness in the initial condition that no teacher has been declared complete increases to 3 teachers or 50% and in the last cycle to 6 teachers or 100%. From the explanation above, it can be concluded that conducting class visits is proven to improve the skills of teachers at SDN 1 Babaktul in using audiovisual media.